Struktur Komunitas Lamun di Perairan Pesisir Manokwari - Lefaan, Paskalina Th.; Setiadi, Dede; Djokosetiyanto, D. (UNIVERSITAS SRIWIJAYA, 2013)
The study was done from July to October 2007 by line transect method, plots, and exploration survey. There were eight species found in this study were grouped into pioneer group (Cymodocea rotundata, Halodule pinifolia, Halodule uninervis, Halophila ovalis, Syringodium isoetifolium) and climax (Cymodocea serrulata, Enhalus acoroides, Thalassia hemprichii), with mixed vegetations. Density, covering percentage and biomass in Andai and Wosi were dominated by H. pinifolia; Rendani and Tj. Mangewa were dominated by T. hemprichii; and Briosi were dominated by C. rotundata and T. hemprichii. INP in Andai and Wosi (dominated by H. pinifolia) were 290.005 and 243.767, respectively; Rendani and Tj. Mangewa (dominated by T. hemprichii) were 101.725 and 135.139, respectively; and Briosi (dominated by C. rotundata) was 120.146. The highest ratio of above and below biomass was found in Andai (7.831) and the lowest was found in Briosi (2.103). Seagrass community in Rendani, Tj. Mangewa and Briosi had higher biodiversity index than Wosi and Andai (0.109 and 0.015). On the other hand, Rendani, Tj. Mangewa, and Briosi had lower dominance index (0.262, 0.421 and 0.338, respectively), compared to Andai (0.989) and Wosi (0.889). Level of similarity among seagrass community in Rendani, Briosi and Tj. Mangewa was categorized as very high (92.31 %), while Andai and Wosi was high (66.67 %).Keywords : seagrass community, pioneer, climax, mixed vegetation, ManokwariMaspari Journal, 2013, 5 (2), 69-81